Environmental Education of costarrican children in school age: Shared responsability by the Ministerio de Educación Pública and home (Biocenosis, 2013)
The article initiates with a short introduction that clarifies the word curriculum as well as the role it accomplishes in education, in the interest of comprehending the responsibility of education in the environmental management of Costa Rica. An official proposal of the Public Education Ministry is set out before the transversal theme: environmental culture for the sustainable development, which at the same time includes four areas of sustainable development and the challenges in which they interact. The competencies that are developed are looked over, aside from the thematic core, the general objective, profile characteristics and contents in which the core is associated for each level of primary education are studied. As a last step, it is imperative for parents to assume, with a share of responsibility, the relation with the formal curriculum to accomplish their children’s environmental education, so that this knowledge affects profoundly in their daily lives and be part of a new and necessary way of assuming the protection of the environment.
Keywords: Education; Social responsibility; Environmental Management; MEP official proposal; Complicity between school and family.